PENDAMPINGAN PENYUSUNAN RPP BERDIFFERENSIASI BAGI GURU SD DI KECAMATAN SETU KABUPETEN BEKASI - Yanti, P. G.; Tarmini, W.; Rismanto, A.; Safi'i, I. (Buletin Udayana Mengabdi; Vol 21 No 2 (2022): Buletin Udayana Mengabdi, 2022)
The differentiated learning implementation plan (RPP) is the design of learning tools that favor student diversity. The purpose of holding this mentoring activity is to provide training in the preparation of lesson plans that take sides for students, improve the professional competence of teachers, and increase the competence of teachers to make differentiated learning effective. The training for the preparation of differentiated lesson plans was attended by elementary school teachers in Setu District, Bekasi Regency. The procedure used in this training activity consists of three stages, namely exploration, elaboration, and confirmation. The training activities that have been carried out can improve the competence of elementary school teachers in the Setu District, Bekasi in preparing a differentiated learning implementation plan (RPP).   Keywords: Learning implementation plan, differentiation